Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T17:01:35+01:00
A)(-5⅔)÷(-2⅚) = (-¹⁷/₃ ) : (-¹⁷/₆ )= ( -¹⁷/₃ ) * (-⁶/₁₇) = 2
b) 0÷(-0,03) = 0
C) (-0,8)÷0,5 = -1,6
D)(1,2)÷(0,03) = 40
e) 3,6÷(-0,9) = -4
f) (-1)÷2½ = (-1) ÷⁵/₂ = (-1) * ⅖ = ⅖
g) 3⅓÷(2²/₉) = ¹⁰/₃ ÷ ²⁰/₉ = ¹⁰/₃ * ⁹/₂₀ = ³/₂ = 1½
h) (-5⅓)÷(-⁸/¹₀) = (-¹⁶/₃) ÷ (-⁸/¹₀) = (-¹⁶/₃) * (-¹⁰/₈) = ²⁰/₃ = 6⅔
2010-02-09T17:52:07+01:00
A. (-5⅔)÷(-2⅚) = 2
b. 0÷(-0,03) = 0
c. (-0,8)÷0,5 = - 1,6
d. (1,2)÷(0,03) = 40
e. 3,6÷(-0,9) = - 4
f. (-1)÷2½ = -0,4
g. 3⅓÷(2²/₉) = 3/2 = 1½
h. (-5⅓)÷(-⁸/¹₀) = 6⅔

jak pomogłem daj naj ;))